Sequence variation in the cellulose synthase (SpCesA1) gene from Shorea parvifolia ssp. parvifolia mother trees - Ho Wei, Seng; Pang Shek, Ling; Pauline, Lau; Ismail, Jusoh (Universiti Putra Malaysia, 2011)
Cellulose synthase (CesA) is a key enzyme involved in the regulation of cellulose biosynthesis pathway. It is heritable and important in determining the variability of wood. In particular, it provides greater impact on the design of future genetic improvement strategies in the production of high quality wood. Thus, the molecular diversity of partial SpCesA1 genomic DNAs (802 bp) generated through PCR amplification was examined in this study, and this followed by sequencing from five selected Shorea parvifolia ssp. parvifolia mother trees. The consensus sequences were aligned to detect the presence of single nucleotide polymorphisms (SNPs). In total, seven SNPs were detected at nucleotide 58, 66, 69, 194, 224, 376 and 448. Interestingly, one single base pair InDel polymorphism was also detected at nucleotide 67. On average, one SNP at every 109 bp of the sequence data was detected. However, this result was obtained from a study of partial SpCesA1 genomic DNA of 802 bp. Two possible restriction enzymes were detected on two SNP sites of partial SpCesA1 genomic DNA. These included EarI (5’-GAAGAG-3’) and EcoRI (5’-GAATTC-3’), which were recognized and later cut at nucleotides 48 and 370, respectively. The exclusiveness of the restriction enzymes EarI and EcoRI obtained for SNPs at nucleotides 58 and 376, respectively, could be useful for the development of cleaved-amplified polymorphic sequence (CAPS) markers which could also be used to understand the molecular diversity of the CesA genes in tropical tree genomes.